(untitled) (International Journal of Banking and Finance, 2010)
This study examined stock market contagion from the United States to the markets of the GCC countries during the period 2007-08. These countries (Bahrain, Kuwait, Oman, Qatar, Saudi Arabia and the United Arab Emirates) were also experiencing accelerating debt levels, overheated real estate markets, and drying up of liquidity. The main hypothesis under investigation is that the collapse of the GCC stock markets did not result purely from contagion, in the sense that these markets did not follow closely the US market during that period. It is argued that local factors were more influential in triggering the collapse and that those markets would have collapsed with or without the global financial crisis. The empirical results show rather limited evidence for the effect of U.S. stock prices on GCC stock prices and a much more important role for oil prices. However, neither of these variables alone can explain the behaviour of GCC stock prices during the period under investigation because of the role played by the domestic factors that caused bubbles and crashes.